Optimization of Parameters of a Planetary Gearbox Using the Taguchi-Grey Relational Analysis - Slavica Miladinovic; Sandra Velickovic; Blaza Stojanovic; Ruzica Nikolic (Communications, 2018)
Optimization of parameters of central gears of a planetary gearbox was performed in this study. Since the optimization of multi-performance characteristics is more complex compared to optimization of a single-performance characteristics, the Taguchi-Grey analysis was used. That approach combines the Taguchi orthogonal array L27 with the Grey relational analysis to determine the influence of the material, module and gear width on the safety coefficient of the planetary gearbox. A Grey relational grade obtained from the Grey relational analysis is used as the performance characteristics in the Taguchi method and Analysis of variance (ANOVA). The optimal combination of parameters for the safety coefficient values was obtained, when the value of the Grey relational grade is 1. Based on the ANOVA analysis, it was established that the most influential parameter is the module, then the gear width and the least influential one is the material.